1977
DOI: 10.1111/j.1365-2265.1977.tb03322.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Plasma Triiodothyronine (T3) Induced by Propranolol

Abstract: The effect of propranolol on plasma triiodothyronine (T3), thyroxine (T4) and triiodothyronine uptake by Sephadex G-25 (RT3U%) was studied in fourteen thyrotoxic patients and eight normal volunteers. 40 mg of propranolol as a single oral dose caused significant reduction in total serum T3 which began 60 min after administration. No significant changes were observed in T4 and RT3U% values. Plasma T3 levels remained suppressed during a 5 day course of treatment with propranolol. These results suggest that propra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(26 citation statements)
references
References 17 publications
4
22
0
Order By: Relevance
“…The iodine content of amiodarone could also be responsible for worsening of hypothyroidism in patients with intact thyroid glands. Although there are reports in humans that propranolol and glucocorticoids also inhibit T4 to T3 conversion (194,195), there do not seem to be data indicating that these agents increase the requirement for L-T4 in hypothyroid patients. Growth hormone (GH) replacement therapy in GH-deficient subjects (196,197).…”
Section: Discussion Of the Clinical Literaturementioning
confidence: 89%
“…The iodine content of amiodarone could also be responsible for worsening of hypothyroidism in patients with intact thyroid glands. Although there are reports in humans that propranolol and glucocorticoids also inhibit T4 to T3 conversion (194,195), there do not seem to be data indicating that these agents increase the requirement for L-T4 in hypothyroid patients. Growth hormone (GH) replacement therapy in GH-deficient subjects (196,197).…”
Section: Discussion Of the Clinical Literaturementioning
confidence: 89%
“…Impaired conversion ofTi to T3 could be an alternative explanation of the low T3 and high T4 :T3 ratio in the CAPD group, particularly as 4 of the CAPD patients but only 1 HD patient were taking ¡3-adrenergic blocking agents which are known to inhibit the peripheral conversion of Ti toT 3 [17], The mean TnTi ratios of the 4 CAPD patients and 7 HD patients not on ^-blocking drugs were 70.6 and 49.5, respectively (NS) as compared with the control group's 46.0 (p<0.05, cf. CAPD group), suggesting that impaired peripheral conversion of T4 to T3 in CAPD patients may occur for reasons other than the use of ¡3-adrenergic blocking agents.…”
Section: Discussionmentioning
confidence: 99%
“…All f3-adrenoceptor blockers seem effective in hyperthyroidism despite a variable influence on the peripheral metabolism of thyroxine and its metabolites (Editorial, Lancet 1980;Perrild etal., 1982). The relieving effect, however, occurs in a few hours while the effect on thyroid hormones is seen within one to two days (Theilade et al, 1977) although some studies have suggested an effect after 3 to 4 h (Lotti et al, 1977). It is therefore not likely that the effect of the /8-adrenoceptor blockers in hyperthyroidism is due to an influence on the metabolism of the thyroid hormones and in agreement with this we were unable to demonstrate any effect of the /32-adrenoceptor agonist terbutaline on the serum concentration of various thyroid hormones.…”
Section: Discussionmentioning
confidence: 99%